Enhancing Sustainable Performance via GHRM: Roles of Green Innovation and Organisational Culture in the Batam Hospitality Sector - Ellen Wu; Agustinus Setyawan (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
The depletion of natural resources and the intensification of climate change have become pressing global challenges for sustainable development. This study examines how Green Human Resource Management (GHRM) influences sustainable performance in the hospitality sector of Batam, with green innovation and organizational culture serving as mediating factors. Using a quantitative approach and Partial Least Squares-Structural Equation Modeling (PLS-SEM), data were collected from 400 respondents working in hotels and resorts. The findings reveal that GHRM significantly enhances sustainable performance, primarily through the mediation of organizational culture and green innovation, with organizational culture emerging as the stronger mediator. These results emphasize the importance of integrating sustainability into human resource strategies to balance operational efficiency, environmental responsibility, and long-term success. Practically, hotels are encouraged to implement green training programs, incorporate environmental criteria into performance evaluations, and establish cross-functional teams to foster innovation and cultural change.